2002
DOI: 10.1038/sj.sc.3101295
|View full text |Cite
|
Sign up to set email alerts
|

Women with spinal cord injury and the impact of aging

Abstract: Objectives: The objectives of this study were to describe what women with longstanding spinal cord injury (SCI) feel they are experiencing as they age, how they are coping and what they require in order to ensure their continued social and economic participation in society. Study design, methods and setting: A naturalistic approach was taken, incorporating three focus groups (n=10) and key informant interviews (n=19) of women with SCI ranging in age from 31 to 70 years and living in rural and urban communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 31 publications
1
58
0
5
Order By: Relevance
“…The majority of women in our sample classified the information they received as insufficient or nonexistent Many of the published studies on the subject with women with SCI do not address the sexual aspect of this condition, 1,6,7,12,23 which highlights the fact that those professionals who provide care and/or rehabilitation for women with these lesions are usually not involved in the important process of sexual readaptation. It is our belief that it is more difficult to adapt without help, and consequently we are in favor of a structured plan of information and integration of women with SCI in their new sexual lives.…”
Section: Discussionmentioning
confidence: 96%
“…The majority of women in our sample classified the information they received as insufficient or nonexistent Many of the published studies on the subject with women with SCI do not address the sexual aspect of this condition, 1,6,7,12,23 which highlights the fact that those professionals who provide care and/or rehabilitation for women with these lesions are usually not involved in the important process of sexual readaptation. It is our belief that it is more difficult to adapt without help, and consequently we are in favor of a structured plan of information and integration of women with SCI in their new sexual lives.…”
Section: Discussionmentioning
confidence: 96%
“…19,20 Moreover, the work of living with pain is compounded by sleep disturbances that result in fatigue, 20 and fatigue is associated with sleep disturbance, depression and pain. 5,8 More research is required before directions of causality can be stated with any confidence.…”
Section: Discussionmentioning
confidence: 99%
“…From their clinical experience the review's authors noted that cognitive complaints (attention, concentration and memory) accompany 'chronic fatigue' in SCI, yet contended that prevention depends on fighting physical deconditioning. This overlooks the identified linkages between overuse and fatigue 1,4,8 and sidesteps the reality that fatigue is not activityspecific (and thus related to specific muscle weakness). 10 Chart review at the GF Strong Rehabilitation Centre in Vancouver, British Columbia (BC) found that 57% of outpatients with SCI of greater than 1-year duration reported fatigue of sufficient severity to interfere with function.…”
Section: Introductionmentioning
confidence: 99%
“…The present study identified the importance of being able to contribute to otherspartners, assistants, families, friends and communities -in reciprocal relationships that foster perceptions of value and competence, connecting and belonging, a finding supported by other researchers. 1,32,33,73,[77][78][79][80][81][82][83][84][85] The important role that special people had played in encouraging autonomy, affirming value and worth and facilitating engagement in meaningful occupations suggests that the rehabilitation process would benefit from the conscious and deliberate inclusion of friends and families. If relationships with special people provide opportunities for reciprocity and for engaging in meaningful occupations following discharge it makes little sense to exclude these people from the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%